Europium ion doped cyan borosilicate glass and preparation method thereof
By optimizing the components and processes of europium ion doped borosilicate glass, the problems of spectral differences in existing cyanoprene LED materials and aging of organic materials are solved, and efficient and stable cyanoprene borosilicate glass preparation is achieved to meet the needs of the cyanoprene LED materials. The application requirements of white light LEDs.
Patent Information
- Application Number
- CN202310767105.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
AI Technical Summary
There are significant differences between the emission spectrum and the natural light emission spectrum of existing green LED materials, and organic materials will discolor and age during long-term use, resulting in a decrease in luminescence quality. Traditional silicate glass preparation temperature is high and costly, making it difficult to meet high efficiency. , stable spectral requirements.
By optimizing the components and processes of europium ion doped borosilicate glass, SiO2, B2O3 and SrO are used as main components, and a glaucoma borosilicate with an optimal emission wavelength of 492nm was prepared at a temperature below 1460°C. Acid glass uses Eu2+ ions as activator to achieve efficient luminescence and stability of the glass.
It realizes high luminescence efficiency matching the characteristic wavelength of the semiconductor chip, reduces the cost of glass preparation, simplifies the process flow, improves the chemical stability and luminescence stability of glass, and meets the application needs of full-spectrum white LEDs.
Smart Images

Figure CN119191707A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of LED materials, and in particular to rare earth europium ion-doped cyan borosilicate glass and a preparation method thereof. Background Art
[0002] Lighting is an important energy activity that consumes a lot of energy, including household and commercial lighting. According to the International Energy Agency, lighting accounts for about 15% of global electricity consumption, and even exceeds 30% in some developed countries. With the increase in global population and economic development, the demand for lighting continues to increase, resulting in a corresponding increase in lighting energy consumption. In order to solve this problem, light-emitting diode (LED) technology has emerged and developed rapidly. Compared with traditional halogen lamps and incandescent lamps, LEDs have obvious advantages, such as longer service life, lower power consumption, more environmental protection, and softer white light color. Therefore, LED is called the "fourth generation" new lighting technology and is widely used around the world. At present, the mainstream technology of white LED is composed of blue InGaN and yellow phosphor Y3Al5O 12 :Ce 3+ (YAG:Ce 3+ ) mixed composition, but there is a significant difference between its emission spectrum and the emission spectrum of natural light. In order to make up for the lack of cyan color in the spectrum, related cyan luminescent materials, including phosphors and fluorescent glass, have attracted widespread attention. In addition, the organic materials used for white light LED packaging will discolor and age during long-term use, reducing their luminous quality, which can be solved by luminescent glass with more stable performance.
[0003] For example, the Chinese patent entitled "Divalent europium activated cyan phosphor and its preparation method and application" (publication number CN 114702955A) discloses a method for preparing a cyan phosphor using Eu2O3. 2+ The patent discloses that Eu can be converted into cyan phosphor by carbon powder without using a reducing atmosphere. 3+ Reduction to Eu 2+ , and then achieve the purpose of cyan light emission. However, the emission wavelength of this phosphor is 460nm, which is not the best cyan emission wavelength. Moreover, after the phosphor and organic components are encapsulated, the LED will become black and aged during long-term use.
[0004] For example, the Chinese patent entitled "A cyan fluorescent glass, its preparation method and full-spectrum LED device" (publication number CN 111003933A) discloses a method for producing a cyan fluorescent glass using Eu 2+ Fluorescent glass is obtained by melting the cyan phosphor as the luminescent center and borosilicate glass. However, this fluorescent glass needs to be melted three times, the operation process is cumbersome, and the process parameters are difficult to control, which greatly increases the cost of large-scale production of glass.
[0005] For example, the Chinese patent entitled "New high-brightness cyan silicate luminescent glass doped with europium ions" (publication number CN 101830638A) discloses a novel high-brightness cyan silicate luminescent glass doped with europium ions. 2+ The cyan luminescent glass with luminescent center is prepared by adding Al to the silicate glass. 3+ Reduction to Eu 2+ , thus achieving cyan luminescence. However, the SiO2 content in silicate glass is as high as 59 mol%, and its preparation temperature is as high as 1560°C, which consumes a lot of energy and is not conducive to reducing the cost of glass growth. Moreover, the patent has not yet disclosed the luminescence properties of cyan silicate glass, such as quantum efficiency and luminescence stability, which are closely related to practical applications.
[0006] In order to solve the above problems existing in the prior art, there is an urgent need in the art to develop a novel cyan glass luminescent material.
[0007] Borosilicate glass is a traditional glass system, including boron oxide, silicon oxide and alkali metal oxide (such as CaO, SrO, BaO). Due to its wide glass-forming area, high transmittance, moderate optical refractive index, good physical and chemical stability, it has become an important glass system and is widely used in optical materials and devices. 2+ The ions have 4f-5d energy level transitions and can emit fluorescence from blue to green under near-ultraviolet light excitation. They have the advantages of high photoelectric conversion efficiency and long fluorescence lifetime, making them one of the preferred luminescence centers for white light LED luminescent materials.
[0008] Therefore, the present invention application aims to disclose a method for preparing a high-efficiency cyan borosilicate glass, and prepare high-performance cyan borosilicate glass by optimizing the components and process of europium ion-doped borosilicate glass, so that it has a good match with the characteristic wavelength of existing commercial semiconductor chips and high luminous efficiency, which well compensates for the deficiency of cyan color in the full spectrum and promotes its widespread application in the field of full-spectrum white light LED lighting. Summary of the invention
[0009] The purpose of the present invention is to provide a cyan borosilicate glass, wherein the cyan here means that the glass has an emission wavelength exceeding 470nm and can reach 492nm at the highest. Specifically, the cyan borosilicate glass with an optimal emission wavelength of 492nm is prepared at a temperature below 1460°C by using oxides SiO2 and B2O3 as network formers and controlling rare earth oxides Eu2O3 and alkaline earth oxides SrO as network modifiers.
[0010] The purpose of this application is also to provide a method for preparing cyan borosilicate glass.
[0011] In order to achieve the above objectives, this application provides the following technical solutions:
[0012] In a first aspect, the present application provides a cyan borosilicate glass, characterized in that the optimal formula components of the glass are:
[0013] SiO2: 20-45 mol%;
[0014] B2O3: 25-55mol%;
[0015] SrO: 20-35 mol%; and
[0016] Rare earth ion activator: 0.05-2.5mol%;
[0017] Wherein, the rare earth ion activator is Eu 2+ ion;
[0018] Among them, the sum of the three components of SiO2, B2O3 and SrO is 100 mol%;
[0019] The concentration of the rare earth ions doped externally or internally is 0.05-2.5 mol% of the sum of the three components of SiO2, B2O3 and SrO.
[0020] In a second aspect, the present application provides a method for preparing the cyan borosilicate glass as described in the first aspect, characterized in that the preparation method comprises the following steps:
[0021] 1): Accurately weigh each raw material according to the glass composition, and mix all the raw materials evenly to obtain a first mixture;
[0022] 2): In a heat-resistant container, the first mixture is melted into a uniform glass melt, the melting temperature required by the glass components is 900-1460° C., the melting time is 50-60 minutes, and the melting atmosphere is air;
[0023] 3): After the uniform glass melt is cast into a mold, it is subjected to constant temperature annealing to eliminate the internal stress of the glass, wherein the annealing temperature of the glass is 300-500° C. and the annealing time is 2-5 hours;
[0024] 4): The cyan borosilicate glass is obtained by cutting, surface grinding and polishing the annealed glass.
[0025] It is characterized in that in step 1), SiO2 in the glass component is introduced through corresponding raw materials, B2O3 is introduced through H3BO3, SrO is introduced through SrCO3, and the activator europium ion is introduced in the form of corresponding rare earth oxides, rare earth fluorides, rare earth carbonates or rare earth nitrate compounds.
[0026] In one embodiment of the second aspect, in step 2), the heat-resistant container comprises an alumina crucible or a platinum crucible.
[0027] In one embodiment of the second aspect, in step 3), the mold comprises a stainless steel mold, and the constant temperature annealing is performed in a muffle furnace.
[0028] In one embodiment of the second aspect, in step 3), it is characterized in that Eu 3+ Ion reduction to Eu 2+ ion.
[0029] In one embodiment of the second aspect, it is characterized in that the excitation peak width of the prepared glass sample is 230-420nm, and the quantum efficiency is as high as 88.57%.
[0030] In one embodiment of the second aspect, it is characterized in that the luminescence stability of the glass is relatively high, which is 55.8% of that at room temperature at 120°C.
[0031] In one embodiment of the second aspect, it is characterized in that the prepared glass sample has an emission peak width of 420-700nm under 410nm excitation, and the strongest emission peak is 492nm blue light.
[0032] In another aspect, the present application provides a cyan borosilicate glass for use in the LED field.
[0033] Compared with the existing published cyan glass technology, the cyan borosilicate glass of the present invention has the following significant features. First, the preparation process is simple, the chemical composition is easy to adjust, large size is easy to achieve, and the chemical stability is good. In particular, the melting temperature required for the cyan borosilicate glass of the present patent application does not exceed 1460°C, which is about 100°C lower than traditional silicate glass, and is of great significance for the energy saving and safety of glass preparation. Secondly, the network formers SiO2 and B2O3 in borosilicate glass have the advantage of low price, and by adjusting the ratio of different network modifiers to change its structure, the Eu in the cyan glass can be easily adjusted. 2+ Finally, there is a wide range of choices for the types and doping amounts of oxides in cyan borosilicate glass, which can effectively regulate the emission wavelength and decay time of cyan glass, so that it can better meet the actual application needs in the LED field. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 : The excitation spectrum of the cyan glass prepared according to Example 1 of the present application and the emission spectrum under 410nm excitation.
[0035] Figure 2This is a quantum yield spectrum of the cyan glass prepared according to Example 1 of the present application.
[0036] Figure 3 : The excitation spectrum of the cyan glass prepared according to Example 2 of the present application and the emission spectrum under 410nm excitation.
[0037] Figure 4 : The excitation spectrum of the cyan glass prepared according to Example 3 of the present application and the emission spectrum under 410nm excitation.
[0038] Figure 5 This is the temperature-dependent spectrum of the cyan glass prepared according to Example 3 of the present application, with room temperature of 25° C. as 100%. DETAILED DESCRIPTION
[0039] Unless otherwise indicated, implied from the context, or customary in the prior art, the tests and characterization methods used are all current as of the filing date of this application. Where applicable, the contents of any patent, patent application, or publication referred to in this application are incorporated herein by reference in their entirety, and their equivalent patent families are also incorporated by reference, especially the definitions of synthesis techniques, products, and processing designs disclosed in these documents in the art. If the definition of a specific term disclosed in the prior art is inconsistent with any definition provided in this application, the definition of the term provided in this application shall prevail.
[0040] In a first aspect, the present application provides a cyan borosilicate glass, characterized in that the raw materials of the glass include the following components:
[0041] SiO2: 20-45 mol%;
[0042] B2O3: 25-55mol%;
[0043] SrO: 20-35 mol%; and
[0044] Rare earth ion activator: 0.05-2.5mol%;
[0045] Wherein, the rare earth ion activator is Eu 2+ ion;
[0046] Among them, the sum of the three components of SiO2, B2O3 and SrO is 100 mol%;
[0047] The concentration of the rare earth ions doped externally or internally is 0.05-2.5 mol% of the sum of the three components of SiO2, B2O3 and SrO.
[0048] In a specific implementation, the present application provides a method for preparing the cyan borosilicate glass as described above, which is characterized by adopting a traditional high-temperature melting method, that is, the glass raw materials are prepared by fully mixing, melting, mold casting and annealing. The specific preparation method includes the following steps:
[0049] S1: accurately weighing the raw materials according to the glass composition, and mixing all the raw materials uniformly to obtain a first mixture;
[0050] S2: In a heat-resistant container, the first mixture is melted into a uniform glass melt, the melting temperature is 900-1460° C. according to the glass components, the melting time is 50-60 minutes, and the melting atmosphere is air;
[0051] S3: After the uniform glass melt is cast into a mold, it is subjected to constant temperature annealing to eliminate internal stress of the glass, wherein the annealing temperature of the glass is 300-500° C. and the annealing time is 2-5 hours;
[0052] S4: Cutting, surface grinding and polishing the annealed glass product to obtain the cyan borosilicate glass.
[0053] In a specific implementation, SiO2 in the glass components is introduced through corresponding raw materials, B2O3 is introduced through H3BO3, SrO is introduced through SrCO3, and the activator ions are introduced in the form of corresponding rare earth oxides, rare earth fluorides, rare earth carbonates or rare earth nitrate compounds, which is beneficial to adjusting the emission wavelength of the glass and optimizing its luminescence performance.
[0054] In a specific implementation, the preparation process of the cyan borosilicate glass described herein is simple, and the melting temperature required for preparing the borosilicate glass of the present invention does not exceed 1460° C. 3+ Ion reduction to Eu 2+ ions. The excitation peak width of the prepared glass sample is 230-420nm, and the quantum efficiency is as high as 88.57%. The luminescence stability of the glass is relatively high, which is 55.8% of that at room temperature at 120°C. The emission peak width of the prepared glass sample under 410nm excitation is 420-700nm, and the strongest emission peak is 492nm blue light.
[0055] In a specific implementation, the present application provides an application of cyan borosilicate glass in the LED field.
[0056] Example
[0057] The present invention will be described in more detail below with reference to the examples. Unless otherwise specified, the raw materials and equipment used in the examples can be purchased through commercial channels and operated under the guidance of the instructions.
[0058] First, we determine the composition ratio of cyan borosilicate glass at a specific temperature. All glass preparation processes are the same, that is, sequentially through glass component batching, grinding, high-temperature melting, casting molding, annealing, cutting and polishing. Among them, the high-temperature melting temperature and time are 900-1450℃ and 50-60min respectively, and the annealing temperature and time are 500℃ and 3h respectively.
[0059] In order to further reflect the characteristics of the rare earth doped cyan borosilicate glass of the present invention, Eu 2+ Ions are used as activators to illustrate the specific implementation process.
[0060] Example 1
[0061] 1. Preparation process
[0062] The specific formula of Example 1 of the present invention is: 30SiO2-40B2O3-30SrO, wherein the activator is Eu 2+ ion,
[0063] It is introduced through Eu2O3, and its external doping concentration is 0.1mol%. The melting atmosphere is air.
[0064] In Example 1, Eu 2+ The preparation steps of cyan borosilicate glass are as follows:
[0065] Step 1: accurately weighing each raw material according to the glass composition, and mixing all the raw materials evenly to obtain a first mixture;
[0066] Step 2: In a heat-resistant container, the first mixture is melted into a uniform glass melt, the melting temperature required by the glass components is 1450° C., the melting time is 55 minutes, and the melting atmosphere is air;
[0067] Step 3: After the uniform glass melt is cast in a mold, it is subjected to constant temperature annealing to eliminate the internal stress of the glass, wherein the annealing temperature of the glass is 500°C and the annealing time is 3 hours;
[0068] Step 4: Cut the glass into 15×20×2.5mm 3 Specifications, Eu obtained after surface grinding and polishing 2+ Cyan borosilicate glass.
[0069] 2. Performance Test
[0070] The room temperature photoluminescence spectrum and quantum yield of the glass were measured using an Edinburgh FLS980 fluorescence spectrometer (Ex slit 0.85 nm, Em slit 0.85 nm). Figure 1It can be seen that the excitation peak is broad, ranging from 230nm to 420nm, which is consistent with the excitation wavelength of most semiconductor chips. The emission spectrum under 410nm excitation is broad-peak emission, covering a wavelength range from 420nm to 700nm, with the strongest emission peak at 474nm. Figure 2 It can be seen that under 300nm excitation, the quantum yield reaches 88.57%.
[0071] Eu of Example 1 2+ The wavelength of cyan borosilicate glass is 474nm. 2+ The excitation and emission spectra of cyan borosilicate glass and the quantum yield spectrum under 300nm excitation are shown in Figure 2. Figure 1 and Figure 2 shown.
[0072] 3. Application
[0073] Eu prepared by the above method 2+ Cyan borosilicate glass can further improve the color rendering index, making LED lighting closer to natural light. It has important application value in the field of white light LED.
[0074] Example 2
[0075] The preparation process is basically the same as that of Example 1, except that the glass composition of Example 2 is: 45SiO2-25B2O3-30SrO, and the activator is Eu 2+ Ions are introduced through Eu2O3, and its external doping concentration is 0.1mol%. The melting temperature is 1430℃, the melting time is 53min, and the melting atmosphere is air.
[0076] Eu of Example 2 2+ The wavelength of cyan borosilicate glass is 492nm. The room temperature photoluminescence spectrum of glass was measured using Edinburgh FLS980 fluorescence spectrometer (Ex slit 0.85nm, Em slit 0.85nm). Figure 3 It can be seen that the excitation peak is broad, ranging from 230nm to 420nm, which is consistent with the excitation wavelength of most semiconductor chips. The emission spectrum under 410nm excitation is broad-peak emission, covering a range from 420nm to 700nm, with the strongest emission peak at 492nm.
[0077] Example 3
[0078] The preparation process is basically the same as that of Example 3, except that the glass composition of Example 3 is: 25SiO2-45B2O3-30SrO, and the activator is Eu 2+Ions are introduced through Eu2O3, and the external doping concentration is 0.4mol%. The melting temperature is 1400℃, the melting time is 58min, and the melting atmosphere is air.
[0079] Eu of Example 3 2+ The wavelength of cyan borosilicate glass is 480nm. The room temperature photoluminescence spectrum of the glass was measured using an Edinburgh FLS 980 fluorescence spectrometer (Ex slit 0.85nm, Em slit 0.85nm). The variable temperature photoluminescence spectrum of the glass was measured using a Beijing Zhuoli Hanguang Omni-A 300i spectrometer. Figure 4 It can be seen that the excitation peak is broad, ranging from 230nm to 420nm, which is consistent with the excitation wavelength of most semiconductor chips. The emission spectrum under 410nm excitation is broad-peak emission, covering a range from 420nm to 700nm, with the strongest emission peak at 479nm. Figure 5 It can be seen that the thermal stability is good.
[0080] Embodiment 4-12
[0081] Table 1 shows the specific formula of Examples 4-12 of the present invention, the activator is Eu 2+ The ions remain unchanged, and the SiO2 content gradually increases from 20mol% to 45mol%. The SiO2 content remains unchanged, and the Eu2O3 gradually increases from 0.075mol% to 1.6mol%. The melting atmosphere is air.
[0082] The preparation process of Examples 4-12 is basically the same as that of Example 1. Specifically, according to the Eu in Table 1, 2+ Formula of Cyan Borosilicate Glass Accurately weigh each component, mix thoroughly and pour into a corundum crucible, then melt in an air atmosphere at 900°C to 1460°C by high temperature melting method for 50-60 minutes; pour the above uniform melt into a preheated 500°C stainless steel mold for casting, and cool naturally to form glass; place the above glass in a muffle furnace at 500°C for 3 hours for annealing treatment to obtain the glass according to Examples 4-12. Cut the glass into 15×20×2.5mm 3 Specifications, Eu obtained after surface grinding and polishing 2+ Cyan borosilicate glass.
[0083] Table 1. Composition of cyan borosilicate glass in Examples 4-12
[0084] Example No. <![CDATA[SiO2]]> <![CDATA[B2O3]]> SrO <![CDATA[Eu2O3]]> Wavelength (nm) Example 4 20 50 30 0.1 472 Example 5 25 45 30 0.1 472 Example 6 35 35 30 0.1 477 Example 7 40 30 30 0.1 484 Example 8 25 45 30 0.075 473 Example 9 25 45 30 0.1 472 Example 10 25 45 30 0.8 481 Embodiment 11 25 45 30 1.2 486 Example 12 25 45 30 1.6 488
[0085] As shown in Table 1, Eu 2+The wavelength of cyan borosilicate glass increases from 472nm to 492nm as SiO2 increases, and increases from 471nm to 488nm as Eu2O3 increases. The wavelength of this series of glasses exceeds 470nm, which enables the glass to better meet the requirements of practical applications.
[0086] The above description of the embodiments is to facilitate those of ordinary skill in the art to understand and apply the present application. It is obvious that those familiar with the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without having to pay creative labor. Therefore, the present application is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the contents disclosed in the present application without departing from the scope and spirit of the present application are within the scope of the present application.
Claims
1. A cyan borosilicate glass, characterized in that: The formula of the cyan borosilicate glass is: SiO2: 10-60 mol%; B2O3: 10-75 mol%; SrO: 10-50 mol%; and Rare earth ion activator: 0.01-5mol%; Wherein, the rare earth ion activator is Eu 2+ ion. Among them, the sum of the three components of SiO2, B2O3 and SrO is 100 mol%; 2. A cyan borosilicate glass, characterized in that: The more optimal formula of the cyan borosilicate glass is: SiO2: 20-45 mol%; B2O3: 25-55mol%; SrO: 20-35 mol%; and Rare earth ion activator: 0.05-2.5mol%; Wherein, the rare earth ion activator is Eu 2+ ion; Among them, the sum of the three components of SiO2, B2O3 and SrO is 100 mol%.
3. The method for preparing cyan borosilicate glass according to claim 1-2, characterized in that: The preparation method comprises the following steps: S1: accurately weighing the raw materials according to the glass composition, and mixing all the raw materials uniformly to obtain a first mixture; S2: In a heat-resistant container, the first mixture is melted into a uniform glass melt, the melting temperature is 900-1460° C. according to the glass components, the melting time is 50-60 minutes, and the melting atmosphere is air; S3: After the uniform glass melt is cast into a mold, it is subjected to constant temperature annealing to eliminate internal stress of the glass, wherein the annealing temperature of the glass is 300-500° C. and the annealing time is 2-5 hours; S4: Cutting, surface grinding and polishing the annealed glass product to obtain the cyan borosilicate glass.
4. The method for preparing cyan borosilicate glass according to claim 3, characterized in that: In step S1, SiO2 in the glass component is introduced through corresponding raw materials, B2O3 is introduced through H3BO3, SrO is introduced through SrCO3, and the activator europium ion is introduced in the form of corresponding rare earth oxides, rare earth fluorides, rare earth carbonates or rare earth nitrate compounds.
5. The method for preparing cyan borosilicate glass according to claim 3, characterized in that: In step S2, the heat-resistant container includes an alumina crucible or a platinum crucible.
6. The method according to claim 3, characterized in that In step S3, the mold includes a stainless steel mold; and the constant temperature annealing is performed in a muffle furnace.
7. The method according to claim 3, characterized in that In air atmosphere, europium ions in borosilicate glass can be converted from Eu 3+ Reduction to Eu 2+ .
8. The method according to claim 3, characterized in that The prepared borosilicate glass has an excitation peak width of 230-420nm, which matches well with the excitation wavelength of commercial LED chips, and the fluorescence quantum efficiency can reach up to 88.57%; And / or, the luminescence stability of the glass is high, which is 55.8% of that at room temperature at 120°C.
9. The method according to claim 3, characterized in that The prepared borosilicate glass has an emission peak width of 420-700nm under 410nm excitation, and the strongest emission peak is 492nm blue light.
10. Application of the cyan borosilicate glass as claimed in claims 1 to 3 in the field of LED.
Citation Information
Patent Citations
Novel europium ion-doped high-brightness cyan silicate light emitting glass
CN101830638A
Cyan fluorescent glass, preparation method thereof and full-spectrum LED device thereof
CN111003933A
Divalent europium activated cyan fluorescent powder as well as preparation method and application thereof
CN114702955A
Chlorine-aluminosilicate fluorescent powder and method for preparing same
CN101307228A
Rare earth doping luminescent glass for white radiation LED and producing thereof
CN101314519A
Cited By
Rare earth doped silicate system high-crystallinity transparent microcrystalline glass and preparation method thereof
CN121063829A
A rare earth doped silicate system high crystallinity transparent glass ceramic and a preparation method thereof
CN121063829B
